Proposed Framework for Activating Digital Green Education in Basic (Al-Farooq Journal of Sciences, 2026)
This study aimed to propose a framework for activating Green Digital Education (GDE) In primary schools through a strategic administrative vision that Integrates digital transformation with environmental sustainability. The study adopted a descriptive analytical approach to review educational literature and determine the requirements for this transformation. The findings Indicate that GDE represents an integrated system for fostering environmental citizenship, and that "Project-Based Learning" (PBL) Is the most effective strategy for Its implementation; furthermore, results showed that structural challenges can be overcome through "Digital Resilience" and human empowerment. Consequently, the study proposed a four-pillar framework comprising: Governance, Smart Infrastructure, Content Development, and Human Empowerment. The study recommends adopting a "Smart Green School Charter" and fostering community partnerships to ensure the sustainability of digital environmental Initiatives, while emphasizing specialized training to enhance teachers' green digital competencies, ensuring a sustainable learning environment capable of adapting to the requirements of the digital age.
Keywords: Green Digital Education, Sustainability, Primary Schools, Proposed Framework, Administrative Vision